Biocultural approach of the association between maturity and physical activity in youth - André O. Werneck; Danilo R. Silva; Paul J. Collings; Rômulo A. Fernandes; Enio R.V. Ronque; Manuel J. Coelho‐e‐Silva; Luís B. Sardinha; Edilson S. Cyrino (Brazilian Society of Pediatrics, 2018)
Objective: To test the biocultural model through direct and indirect associations between biological maturation, adiposity, cardiorespiratory fitness, feelings of sadness, social relationships, and physical activity in adolescents. Methods: This was a cross‐sectional study conducted with 1,152 Brazilian adolescents aged between 10 and 17 years. Somatic maturation was estimated through Mirwald's method (peak height velocity). Physical activity was assessed through Baecke questionnaire (occupational, leisure, and sport contexts). Body mass index, body fat (sum of skinfolds), cardiorespiratory fitness (20‐m shuttle run test), self‐perceptions of social relationship, and frequency of sadness feelings were obtained for statistical modeling. Results: Somatic maturation is directly related to sport practice and leisure time physical activity only among girls (β = 0.12, p < 0.05 and β = 0.09, respectively, p < 0.05). Moreover, biological (adiposity and cardiorespiratory fitness), psychological (sadness), and social (satisfaction with social relationships) variables mediated the association between maturity and physical activity in boys and for occupational physical activity in girls. In general, models presented good fit coefficients. Conclusion: Biocultural model presents good fit and emotional/biological factors mediate part of the relationship between somatic maturation and physical activity. Resumo: Objetivo: Testar o modelo biocultural por meio de associações diretas e indiretas entre maturação biológica, adiposidade, capacidade cardiorrespiratória, sentimentos de tristeza, relacionamentos sociais e atividade física em adolescentes. Métodos: Este foi um estudo transversal feito com 1.152 adolescentes brasileiros entre 10 e 17 anos. A maturação somática foi estimada por meio do método de Mirwald (pico da velocidade de crescimento). A atividade física foi avaliada por meio do questionário de Baecke (contextos ocupacional, lazer e prática de esportes). Foram obtidos o índice de massa corporal, gordura corporal (soma de dobras cutâneas), capacidade cardiorrespiratória (teste shuttle run de 20 metros), autopercepções de relação social e frequência de sensação de tristeza para modelagem estatística. Resultados: A maturação somática mostrou‐se diretamente relacionada à prática de esportes e à atividade física de lazer somente entre meninas (β = 0,12, p < 0,05 e β = 0,09, respectivamente, p < 0,05). Ademais, as variáveis biológicas (adiposidade e aptidão cardiorrespiratória), psicológica (tristeza) e social (satisfação com os relacionamentos sociais) mediaram a associação entre maturação e atividade física em meninos e para atividade física ocupacional em meninas. Em geral, os modelos apresentaram bons coeficientes de ajuste. Conclusão: O modelo biocultural apresenta bom ajuste e fatores emocionais/biológicos mediam parte da relação entre maturação somática e atividade física. Keywords: Adolescent, Child, Maturity, Motor activity, Palavras‐chave: Adolescente, Criança, Maturação, Atividade motora